Caracterização bioquímico-farmacológica de uma PLA2 ácida isolada da peçonha de Bothropoides pauloensis (Bothrops paulo-ensis) - Ferreira, Francis Barbosa (2011)
The phospholipases A2 are small molecules, with molecular mass from 13 to 18 kDa, and one of the most abundant components present in the botropics/botropoics snake venoms, exerting a variety of toxic effects as neurotoxicity, myotoxicity, citotoxicity, anti or pro-platelet aggregation, and others. Most of the toxic PLA2 are basic proteins, therefore, the acid PLA2s isoforms and their possible roles are less understood. In this work, we described the purification and physic-chemical and pharmacological characterization of an acidic phospholipase A2 from Bothropoides pauloensis. This enzyme, named BpPLA2-TXI, was purified through four chromatographic steps and it represents 2,4% of the snake venom. It is a monomeric protein with 13.6 kDa by MALDI-TOF and theoretical isoeletric point of 4,98. The codified cDNA was obtained by RT-PCR from venom gland total RNA, utilizing oligonucleotides based on the amino acids partial sequences for this toxin. The N-terminal sequence (fourty-eight amino acids residues) as well as the complete sequence deduced by cDNA, show 122 amino acids residues which revealed significant similarity with other acidic Asp49 PLA2. BpPLA2-TXI is catalytically active, with specific activity of 142 U/mg and it is thermo- and pH-stable. Besides its catalytic activity, BpPLA2-TXI displayed some farmacological effects, as inhibited platelet aggregation induced by collagen or ADP, induced edema and myotoxicity. The phylogenetic analyses shows that BpPLA2-TXI forms a group with other acidic PLA2 Asp49 from Bothropoides and Bothrops genus, wich are characterized by the a catalytic activity associated with anti-platelet effects.